On the peculiarities of electrical conductivity in ARC plasma containing stainless steel and tungsten - Porytskyy, P.V. (Вопросы атомной науки и техники, 2018)
The influence of stainless steel and tungsten impurities on the electrical conductivity of multicomponent arc plasma is considered in the ambient atmosphere of argon and air. The calculations are carried out on the base of Grad’s method, and it is shown that a small amount of metal causes the essential changes in the values of electrical conductivity in comparison with the case of pure gaseous mixtures. It is revealed that the increasing of metal concentration leads to the decreasing of electrical conductivity under the certain conditions in arc plasmas.